A review of guidelines for including wider economic impacts in transport appraisal. Issue 1 (2nd January 2017) - Wangsness, Paal Brevik; Rødseth, Kenneth Løvold; Hansen, Wiljar
ABSTRACT: In this paper we examine how 23 industrialised countries treat wider economic impacts (WEIs) in transport appraisals. We identify 12 different types of impacts based on these countries' appraisal guidelines. Agglomeration impacts and Production changes in imperfect markets are the most widely accepted, being recognised by 14 and 10 countries, respectively. However, about half of the impacts are mentioned by only one country, and few recommend including the impacts directly in cost–benefit analyses. Several countries provide provisos or criteria that must be met before WEIs can be assessed in the first place. We found method recommendations for quantifying WEIs in 10 countries. However, with the exception of the UK Department for Transport's (DfT) methodological framework, there is very little international consensus on the choice of appropriate methods. Our findings thus supplement and reinforce the conclusions from the Norwegian Official Report of the Hagen Committee [NOU 2012:16. (2012). Samfunnsøkonomiske analyser . Oslo: Departementenes servicesenter] that there is currently no established consensus on the magnitude and relevance of WEIs, or on how and which of these impacts should be taken into account in transport appraisals. Recommendations for further research and appraisal practices are provided.